Hallux rigidus: current concepts review and treatment algorithm with special focus on interposition arthroplasty - Di Caprio, Francesco; Mosca, Massimiliano; Ceccarelli, Francesco; Caravelli, Silvio; Vocale, Emanuele; Zaffagnini, Stefano; Ponziani, Lorenzo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work: Hallux rigidus represents a surgical challenge, with a multitude of possible surgical options, but with no ideal procedures. The propose of this paper was to review the actual knowledge on the operative techniques, paying particular attention to the evolution of interposition arthroplasties, as an alternative to arthrodesis and prosthesis in the advanced stages of the disease. Methods: A comprehensive literature PubMed search was performed, and the actual literature regarding hallux rigidus was overviewed. The operative and nonoperative options for HR were described. Studies on interposition arthroplasty were classified by publication year, summarizing the operative technique, results and complications. Results: Among the various techniques for interposition arthroplasty, the Modified Oblique Keller Interposition Arthtoplasty (MOKCIA) showed the lower complication rate. It does not sacrifice the insertion of the flexor halluces brevis, maintaining the stability, length and strength of the big toe. Conclusions: Although long-term randomized controlled trials are lacking for interposition arthroplasties, the reported results are comparable to the other alternatives for the treatment of end-stage hallux rigidus, making this technique a valid alternative also in the young active patient, without precluding other end-stage procedures in case of failure. Based on the current knowledge, a treatment algorithm was developed, according to the Coughlin classification.